2018
DOI: 10.1016/j.apsusc.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printed doped polyaniline: Navigating through physics and chemistry for the next generation devices

Abstract: Innovative benzidine-free PANI-based inks for electrically conductive inkjet printed devices were developed and tested and the results compared with those obtained by traditional PANI. NMR investigations evidenced the presence of quinones and phenolic groups on the backbone of the innovative PANIs that are thought being responsible for the higher solubility in DMSO. A mechanism of reaction was proposed. The numerous characterizations (NMR, UV-Vis, FTIR, XPS and electrical investigations) allowed to compare pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The weight percentage of doped metal and the atomic ratio of metal to coordinated nitrogen were quantified and listed in Table 1. It is confirmed that the chemical composition of the synthesized EB-PANI is in accordance with the reported molecular structure [27,28], alongside slight oxidation and residual chlorine content from the polymerization process.…”
Section: Physical and Chemical Properties Of The Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…The weight percentage of doped metal and the atomic ratio of metal to coordinated nitrogen were quantified and listed in Table 1. It is confirmed that the chemical composition of the synthesized EB-PANI is in accordance with the reported molecular structure [27,28], alongside slight oxidation and residual chlorine content from the polymerization process.…”
Section: Physical and Chemical Properties Of The Samplessupporting
confidence: 83%
“…It is believed that the fluorinated groups of the ionomer could increase the hydrophobicity of the electrode and promote the selectivity toward the reduction of CO 2 rather than protons [41]. However, the terminal chain sulfonic groups in Nafion lead to an increase in the overall surface polarity [27], resulting in the enhancement in the HER. The co-presence of Nafion and CB further enhances the HER activity, while CB alone does not add any significant beneficial effect for the CO 2 RR (Fig.…”
Section: Investigation Of the Electrode Compositionmentioning
confidence: 99%
“…Moreover, it should be emphasized that the VB edge is far below the Fermi level in the ACC substrate, but the growth of PAni increases the density of states near the Fermi energy to delineate a small shoulder at ~4 eV. A similar VB pattern has been reported earlier for PAni films, although the relative peak intensity and resolution of the various peaks is highly dependent on the particular intrinsic redox state, the doping and protonation levels, and the nature of the dopant ion [46,47,48]. Nakajima et al [46] reported a set of peaks in the region 10–20 eV (17.5 eV, 14 eV and 11.5 eV) due to an overlap of molecular orbitals involving benzenoid C and N in leucoemeraldine salt, while the electron density close to the Fermi level was found to be characteristic of a conjugated structure of double and single bonds.…”
Section: Resultssupporting
confidence: 66%
“…Nakajima et al [46] reported a set of peaks in the region 10–20 eV (17.5 eV, 14 eV and 11.5 eV) due to an overlap of molecular orbitals involving benzenoid C and N in leucoemeraldine salt, while the electron density close to the Fermi level was found to be characteristic of a conjugated structure of double and single bonds. More recently, Bocchini et al [48] distinguished a C2s peak at 13 eV, a 9–11 eV feature corresponding to a C–N 2p-σ state, and a group of weak photoemission peaks below 8 eV assigned to C2p-σ and C2p-π bands in polyemeraldine doped with camphorsulphonic or aminosulphonic acids. Hybrid PAni-ACC composites formed at intermediate electropolymerization times (Figure 6b) show mixed features from both the underlying carbon matrix and a polymer thin film.…”
Section: Resultsmentioning
confidence: 99%
“…The world produces more than 50 million tons of e‐waste each year, worth over $62.5 billion, among which only 20% of this is formally recycled . However, we cannot stay away from this faster digitalization where tremendous advancement in wearables and portable smart electronics imposes low‐cost, wireless, and light energy sources that must include green and sustainable materials/technologies to become effective in reducing e‐waste. When it comes to portability, cost effectiveness and green technology altogether, the contribution of energy harvesters which convert the wasted energy from ambient environment or human body motion into electrical energy for diverse applications is an absolute accomplisher …”
Section: Introductionmentioning
confidence: 99%